2011
DOI: 10.3171/2011.5.peds1139
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of nonaccidental head trauma in infants associated with the economic recession

Abstract: Object Nonaccidental head trauma (NAHT) is a major cause of death in infants. During the current economic recession, the authors noticed an anecdotal increase in infants with NAHT without an increase in the overall number of infants admitted with traumatic injuries. An analysis was performed to determine whether there was an association between economic recession and NAHT. Methods With Institutional Revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
48
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 6 publications
1
48
3
3
Order By: Relevance
“…[9][10][11] However, our study did not find a statistically significant increase in the rate of AHT nationally, regionally, or There are limitations to the current study. First, although the KID data set includes a large sample of all hospital discharges, it does not include the whole universe of pediatric discharges.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…[9][10][11] However, our study did not find a statistically significant increase in the rate of AHT nationally, regionally, or There are limitations to the current study. First, although the KID data set includes a large sample of all hospital discharges, it does not include the whole universe of pediatric discharges.…”
Section: Discussioncontrasting
confidence: 39%
“…Three recent hospital-based studies [9][10][11] suggest that the number of cases of AHT in young children rose dramatically in parallel with the US recession of 2007 to 2009. None of these analyses examining AHT included complete state, regional, or national population-level data.…”
mentioning
confidence: 99%
“…Another study demonstrated an increase in the number and severity of AHT cases during the recession compared with the period before the recession. 19 Finally, a study using a national sample of emergency department data reported that rates of AHT in children 4 years old or younger were higher during 2007 and 2008 compared with 2006 and 2009, suggesting an increase in AHT during the recession. 20 A recent systematic review of pediatric studies evaluating the impact of the great recession on health behaviors, child physical abuse, mental health, and health-related quality of life concluded that "the evidence to date demonstrates the plausibility of the association between the crisis and violence against children."…”
Section: Discussionmentioning
confidence: 98%
“…28,32 Although the individual poverty of a child's family has been recognized as a risk factor for abuse 4,34,35 and for hospitalization from abuse, 7, 10 the relationship of community poverty on fatal child abuse is less well understood. 14,36,37 Local studies have noted increased rates of child abuse in impoverished communities. 28, 38, 39 In this study, we analyzed the association between community poverty and fatal child abuse at the national level and demonstrated a consistent association between community poverty concentration and child abuse fatalities across the study period.…”
Section: Discussionmentioning
confidence: 99%